2021
DOI: 10.46661/ijeri.5588
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 in Turkey: Leisure Boredom, Psychological Resilience, Physical Activity and Emotional State

Abstract: Bu araştırma, boş zamanlardaki bireylerin can sıkıntısı algısı ile psikolojik dayanıklılık düzeyleri arasındaki ilişkiyi incelemek ve bireylerin boş zaman aktiviteleri, fiziksel aktiviteye katılım ve duygusal durumlarını tanımlamak için CoViD-19 salgınında uygulanan karantina sürecinde yapılmıştır. durum. Buna göre Türkiye'de yaşayan 2214 gönüllü kişi 909 erkek (% 41,1) ( yaş = 33,83 ± 10,73) ve 1305 kadın (% 58,9) ( yaş = 32,41 ± 10,02) ile katıldı. Çalışma kapsamında araştırmacılar tarafından oluşturulan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
0
4
0
2
Order By: Relevance
“…On the individual (student) level, healthy lifestyle behaviours (exercising, spending time outdoors [ 47 ], eating well, good quality sleep [ 48 ]) and emotion-focused coping strategies (relaxation techniques [ 49 ], mindfulness techniques, and philosophical and moral reflections [ 50 ]) have been associated with better psychological wellbeing in children during COVID-19. In our findings, children who engaged in regular physical activity (e.g., socially distanced bicycle riding with friends) or practiced mindfulness, found those activities to be helpful in coping with stress, boredom, and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…On the individual (student) level, healthy lifestyle behaviours (exercising, spending time outdoors [ 47 ], eating well, good quality sleep [ 48 ]) and emotion-focused coping strategies (relaxation techniques [ 49 ], mindfulness techniques, and philosophical and moral reflections [ 50 ]) have been associated with better psychological wellbeing in children during COVID-19. In our findings, children who engaged in regular physical activity (e.g., socially distanced bicycle riding with friends) or practiced mindfulness, found those activities to be helpful in coping with stress, boredom, and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…At the time the current study was written (April, 2021), the effect of Covid-19 was still continuing on the world, and the pandemic has caused various physical and psychological problems in high school students, as well as in individuals of all ages. Previous study results showed positive correlation with participation in physical activity and psychological resilience and negative correlation with leisure boredom (Dursun et al, 2021 ) during the Covid-19 lock down. Therefore, increased participation in physical activity and exercise during this period will increase the physical, psychological and sociological benefits we will derive from our leisure experience especially for female high school students.…”
Section: Recommendationsmentioning
confidence: 81%
“…Researches on PA during COVID-19 show that it was associated with higher resilience [46,63], less negative affect [23,37,46], and better psychological wellbeing [64,65]. Although there have been kinds studies in the literature revealing the association between PA and general negative affect such as depression and anxiety, the relationship between PA and PHENA is still unclear.…”
Section: The Present Study and Hypothetical Modelmentioning
confidence: 99%